Examining the relationships among health-related quality-of-life indicators in cancer patients participating in clinical trials: a pooled study of baseline EORTC QLQ-C30 data. (October 2011) - Martinelli, Francesca; Quinten, Chantal; Maringwa, John T; Coens, Corneel; Vercauteren, Jurgen; Cleeland, Charles S; Flechtner, Henning; Gotay, Carolyn; Greimel, Eva; King, Madeleine; Mendoza, Tito; Osoba, David; et al.
Aims: Cancer patients experience multiple and concurrent health-related problems and symptoms due to their illness and therapies. The first objective of this analysis was to identify how health-related quality-of-life (HRQoL) indicators cluster among cancer patients and how possible clusters change across patients with different sociodemographic and clinical characteristics. The second objective of this study was to identify which HRQoL indicators are linked to patients'' perception of overall quality of life.Methods: Retrospective pooling of 30 closed randomized European Organisation for Research and Treatment of Cancer (EORTC) clinical trials yielded baseline EORTC Quality of Life Core Questionnaire (QLQ-C30) HRQoL data for a total of 7417 patients. A cluster analysis was performed to determine how the 15 HRQoL indicators obtained with the QLQ-C30 cluster overall and by patient characteristics.Results: Three main clusters emerged from the overall dataset: a physical cluster, a psychological cluster and a gastrointestinal cluster. The same clusters were found in subgroups defined according to sociodemographic and clinical characteristics, while some differences emerged among cancer sites. The Global Health scale was found to be part of the physical cluster in the overall dataset. This result was consistent across different levels of disease severity, while divergent results were seen across some cancer sites.Conclusion: Our findings suggest that HRQoL indicators are interrelated. Understanding these relationships may aid clinicians in managing the symptom burden experienced by patients, as well as policy-makers, in defining psychosocial support plans.